Enhanced Attraction of Arthropod Vectors to Infected Vertebrates: A Review of Empirical Evidence - Cozzarolo, Camille-Sophie; Glaizot, Olivier; Christe, Philippe; Pigeault, Romain (Frontiers in Ecology and Evolution, 2020)
A large diversity of parasites manipulates their hosts in various ways to complete their own life cycle. Enhancing the attractiveness of their host to vectors has been suggested as a strategy al-lowing vector-borne parasites to increase their transmission. Indeed, a higher attraction of he-matophagous, arthropod vectors to infected vertebrates compared to uninfected individuals has been found in many systems (e.g. Trypanosoma-tsetse flies, Leishmania-sand flies, Borrelia-ticks) but was most often verified in the Plasmodium-mosquitoes model. However, a number of studies found no difference in attractiveness, or a higher attractiveness of uninfected hosts. In this review, we present studies reporting a comparison of the attractiveness and/or the biting rate of infected and uninfected vertebrates. We then discuss several biological factors and exper-imental design aspects that can explain discrepancies between studies. Finally, we stress the im-portance of investigating the mechanisms of parasite-induced increased attractiveness of infected hosts to conclude that such observations are cases of adaptive manipulation.